Perlindungan Hukum terhadap Masyarakat Nagari yang Tanahnya Disertifikatkan Secara Melawan Hukum (Studi Putusan Mahkamah Agung Nomor 3818 K/PDT/2023) - Ferdian, Muhamad Wira; Yustikarini, Meliyana (Wajah Hukum, 2025)
This research aims to analyze the legal protection for nagari communities experiencing illegal land certification, as well as to evaluate the implementation of the Supreme Court's decision in resolving customary land disputes to prevent similar cases from recurring in the future. The research method used is normative juridical through legislation as the main technique in data collection and examining Supreme Court decision number 3818 K/PDT/2023, related to references from books, journals, and other materials. The research results indicate that indigenous communities whose land has been unlawfully certified are entitled to request the annulment of land rights on the grounds of administrative defects. This cancellation process can be carried out through a ministerial decree as regulated in Articles 105 and 106 of the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 9 of 1999 concerning the Procedures for Granting and Cancelling State Land Rights and Management Rights.